2022
DOI: 10.1001/jamanetworkopen.2021.44093
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Clinical Palliative Care Trigger Status vs Actual Needs Among Critically Ill Patients and Their Family Members

Abstract: IMPORTANCEPalliative care consultations in intensive care units (ICUs) are increasingly prompted by clinical characteristics associated with mortality or resource utilization. However, it is not known whether these triggers reflect actual palliative care needs. OBJECTIVE To compare unmet needs by clinical palliative care trigger status (present vs absent). DESIGN, SETTING, AND PARTICIPANTS This prospective cohort study was conducted in 6 adult medical and surgical ICUs in academic and community hospitals in No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…We observed that palliative care needs reported by ICU patients’ family members were common, complex, and persistent, with one-third still experiencing serious overall needs after a week of ICU care. These results are compelling because while palliative care needs are common (8, 25), it has generally been assumed that they improve over time in ICU settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that palliative care needs reported by ICU patients’ family members were common, complex, and persistent, with one-third still experiencing serious overall needs after a week of ICU care. These results are compelling because while palliative care needs are common (8, 25), it has generally been assumed that they improve over time in ICU settings.…”
Section: Discussionmentioning
confidence: 99%
“…As such, this metric could potentially play a useful role in future trials of ICU-based interventions. Last, knowledge of need severity and type could be used to inform future models of ICU-based palliative care delivery focused on efficiently aligning the skills of the ideal provider (e.g., nurse, chaplain, social worker, physician) with the needs of greatest importance (8, 36).…”
Section: Discussionmentioning
confidence: 99%
“…Patients in ICUs and family members have substantial heterogeneity in sociodemographic and clinical characteristics, none of which appear to adequately reflect the presence, type and severity of palliative care needs present 12. This represents a challenge to aligning the appropriate type of care with the specific unmet needs.…”
Section: Discussionmentioning
confidence: 99%
“…A key clinical challenge in ICU settings is identifying those who possess serious unmet needs with accuracy and efficiency, and then aligning the most appropriate provider with the patient and family member. We recently found that clinical factors such as common clinical palliative care triggers and illness severity performed no better than chance at identifying family members with serious palliative care needs in ICU settings 12. As such, if the goal is to address unmet palliative care needs, they must be ascertained directly from patients and family members—a task that is feasible,34 though more challenging than building an electronic health record system-informed screening algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation